2003
DOI: 10.1152/ajpregu.00554.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peptide histidine isoleucine on consummatory behavior in rats

Abstract: . Effect of peptide histidine isoleucine on consummatory behavior in rats. Am J Physiol Regul Integr Comp Physiol 284: R1445-R1453, 2003. First published February 20, 2003 10.1152/ajpregu.00554.2002-Peptide histidine isoleucine (PHI) and VIP are derived from the same precursor. While central VIP decreases food intake, potential effects of PHI on feeding have not been studied. In the current study, we found that PHI administered intracerebroventricularly (ICV) or into the hypothalamic paraventricular nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This was due to an increase in DMI and resulted in more milk and milk protein, but no increase in milk protein percent. It is not known why Hisduo should cause an increase in DMI in lactating cows when it is known that His is a potent inhibitor of feed intake in rats either through formation of histamine (Kasaoka et al, 2004) or through conversion to histidine peptides (Olszewski et al, 2003 (Forslund et al, 2000;Burke et al, 2012) do not appear in this database for dairy cattle. This may be because of the more or less constant flow of nutrients supplied to the ruminant (Nocek and Braund, 1985) and the relatively small range of dietary protein tested in dairy rations generally and in the current database (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This was due to an increase in DMI and resulted in more milk and milk protein, but no increase in milk protein percent. It is not known why Hisduo should cause an increase in DMI in lactating cows when it is known that His is a potent inhibitor of feed intake in rats either through formation of histamine (Kasaoka et al, 2004) or through conversion to histidine peptides (Olszewski et al, 2003 (Forslund et al, 2000;Burke et al, 2012) do not appear in this database for dairy cattle. This may be because of the more or less constant flow of nutrients supplied to the ruminant (Nocek and Braund, 1985) and the relatively small range of dietary protein tested in dairy rations generally and in the current database (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that adiponectin specifically hyperpolarizes oxytocin neurons thus inhibiting action potential generation and ultimately oxytocin release. Although many central signals involved in the regulation of energy balance including leptin (Hakansson et al 1998; Ur et al 2002), cocaineā€“amphetamineā€related transcript (Vrang et al 2000), CCK (Olson et al 1992; Ueta et al 1993) and PHI (Olszewski et al 2003) play critical roles in controlling oxytocin secretion, the precise role of this neurohypophysial peptide in the regulation of energy balance has yet to be established. Modified serum concentrations of oxytocin have been reported in pathological states of energy imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that magnocellular neurons depolarize in response to leptin administration supporting the hypothesis that these neurons are sensitive to adiposity hormones (Powis et al 1998) and therefore the circulating concentrations of neurohypophysial peptides may be regulated by adipokines. Intriguingly, oxytocin neurons in the PVN have been suggested to play a vital role in coordinating feeding cessation (Olson et al 1991 a , b ; Verbalis et al 1993; Blevins et al 2003) by acting as targets for factors which induce anorexigenic behaviour such as CCK (Olson et al 1992) and peptide histidine isoleucine (PHI) (Olszewski et al 2003). The concentrations of oxytocin in brain and periphery have also been shown to be compromised during pathological states of energy homeostasis such as obesity (elevated) (Stock et al 1989) and restrictive anorexia (reduced) (Demitrack et al 1990).…”
mentioning
confidence: 99%
“…The i.c.v. administration and intra-PVN or -CeA injection of PHI decreased food consumption in overnight-deprived rats ( 205 ). These peptidesā€™ roles in appetite regulation has not been well understood, hence further research is warranted for clarity in understanding the role of these peptides in neuromodulation of feeding behavior.…”
Section: Other Peptidesmentioning
confidence: 99%